2022
DOI: 10.1108/lht-11-2021-0393
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social media use on critical thinking ability of university students

Abstract: PurposeThis research aims to discover the relationship between social media usage (SMU) and the critical thinking ability (CTA) of university students, and to answer the question that whether social media dependence (SMD) affects the development of CTA, and thus providing a reference for the social media access strategy of academic libraries from the perspective of media information literacy.Design/methodology/approachThe research data were collected via 300 valid questionnaires whose respondents are students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 85 publications
1
5
0
Order By: Relevance
“…Social media and library and information services Social media is particularly impactful to the younger generation, not just in their daily lives but also in their learning (Leung et al, 2021;Wang et al, 2021;Lei et al, 2021;Dong et al, 2021;Cheng et al, 2022;Wang and Xie, 2022;Dong et al, 2021;Wang et al, 2022b). Thus, library services also need to be promoted and provided on social media (Chan et al, 2020b;Cheng et al, 2020;Fong et al, 2020;Lam et al, 2022;Guo et al, 2022;Yang et al, 2022).…”
Section: Transformation Of Librariesmentioning
confidence: 99%
“…Social media and library and information services Social media is particularly impactful to the younger generation, not just in their daily lives but also in their learning (Leung et al, 2021;Wang et al, 2021;Lei et al, 2021;Dong et al, 2021;Cheng et al, 2022;Wang and Xie, 2022;Dong et al, 2021;Wang et al, 2022b). Thus, library services also need to be promoted and provided on social media (Chan et al, 2020b;Cheng et al, 2020;Fong et al, 2020;Lam et al, 2022;Guo et al, 2022;Yang et al, 2022).…”
Section: Transformation Of Librariesmentioning
confidence: 99%
“…In this issue, Cheng et al (2024) examine the relationship between social media usage (SMU) and the critical thinking ability (CTA) of university students and found that SMU is a double-edged sword, narrowing the digital gap in terms of accessibility but widening the digital gap in terms of usage. Chen and Chen (2024) show that the mobile information environment significantly impacts perceived usefulness and ease of use for learning.…”
Section: Transforming Learning With Mobile Technologiesmentioning
confidence: 99%
“…In the present paper, we tried to acknowledge the key role of social media use in beliefs in conspiracy theories. Based on the distinction between active and passive social media use and judging from the role of active engagement with social media in enhancing critical thinking and literacy (Cheng et al, 2022;Xu et al, 2019)-two consistently negative predictors of conspiracy beliefs (Swami et al, 2014), we hypothesize that:…”
Section: Social Media Use and Believing In Conspiracy Theoriesmentioning
confidence: 99%
“…In the present paper, we tried to acknowledge the key role of social media use in beliefs in conspiracy theories. Based on the distinction between active and passive social media use and judging from the role of active engagement with social media in enhancing critical thinking and literacy (Cheng et al., 2022; Xu et al., 2019)—two consistently negative predictors of conspiracy beliefs (Swami et al., 2014), we hypothesize that: Social media use will be related with endorsement of conspiracy theories. This prediction is specified to two directional hypotheses: Hypothesis Active social media use will be negatively correlated, while passive social media use will be positively correlated with beliefs in conspiracy theories (Study 1). Hypothesis Likewise, investigating causal effects through manipulation of social media use, we hypothesize that active social media use will have a negative effect, and passive social media use will have a positive effect, on beliefs in conspiracy theories (Study 2).…”
Section: Social Media Use and Believing In Conspiracy Theoriesmentioning
confidence: 99%